Expression, purification, crystallization and preliminary X‐ray analysis of CttA, a putative cellulose‐binding protein from Ruminococcus flavefaciens. Issue 6 (1st June 2015) - Venditto, Immacolata; Bule, Pedro; Thompson, Andrew; Sanchez‐Weatherby, Juan; Sandy, James; Ferreira, Luis M. A.; Fontes, Carlos M. G. A.; Najmudin, Shabir
<x xml:space="preserve">Abstract</x> A number of anaerobic microorganisms produce multi‐modular, multi‐enzyme complexes termed cellulosomes. These extracellular macromolecular nanomachines are designed for the efficient degradation of plant cell‐wall carbohydrates to smaller sugars that are subsequently used as a source of carbon and energy. Cellulolytic strains from the rumens of mammals, such as Ruminococcus flavefaciens, have been shown to have one of the most complex cellulosomal systems known. Cellulosome assembly requires the binding of dockerin modules located in cellulosomal enzymes to cohesin modules located in a macromolecular scaffolding protein. Over 220 genes encoding dockerin‐containing proteins have been identified in the R. flavefaciens genome. The dockerin‐containing enzymes can be incorporated into the primary scaffoldin (ScaA), which in turn can bind to adaptor scaffoldins (ScaB or ScaC) and subsequently to anchoring scaffoldin (ScaE), thereby attaching the whole complex to the cell surface. However, unlike other cellulosomes such as that from Clostridium thermocellum, the Ruminococcus species lack a specific carbohydrate‐binding module (CBM) on ScaA which recruits the entire complex onto the surface of the substrate. Instead, a cellulose‐binding protein, CttA, comprising two putative tandem novel carbohydrate‐binding modules and a C‐terminal X‐dockerin module, which can bind to the cohesin of ScaE, may mediate the attachment of bacterial cells to cellulose. Here, the expression, purification and crystallization of the carbohydrate‐binding modular part of the CttA from R. flavefaciens are described. X‐ray data have been collected to resolutions of 3.23 and to 1.61 Å in space groups P3121 or P3221 and P21, respectively. The structure was phased using bound iodide from the crystallization buffer by SAD experiments.